Pain increases motivational drive to obtain reward, but does not affect associated hedonic responses: A behavioural study in healthy volunteers. (24th January 2013) - Gandhi, W.; Becker, S.; Schweinhardt, P.
Abstract Background Pain and reward have been suggested to interact, and some evidence is provided by a rodent study showing that acutely injured animals are more motivated to reach a food reward while they do not increase food consumption, pointing at unaltered reward liking. Since no data exist in humans, we conducted a psychophysical experiment to test the effects of experimentally induced tonic pain on (1) the motivation to receive reward and (2) hedonic responses when being rewarded. Methods Forty healthy participants underwent two experimental sessions: in one, painful heat stimulation was continuously applied while participants played a monetary reward task; in the other, participants experienced non‐painful warm stimulation while playing the task. In the task, participants needed to react quickly enough to a target cue to win the money associated with the particular trial ($0.04, $1 or $4). Reaction time to the target cue served as measure of motivation. Ratings after each trial on how much the participant liked the trial's outcome served as a measure of hedonic responses. Results Pain increased the motivation to obtain reward when the incentive was high, indexed by decreased reaction times (repeated‐measures analysis of variance, interaction pain × incentive; p = 0.009). In contrast to motivational drive, hedonic ratings of the rewarding stimuli were not influenced by pain. Conclusion Similar to existing rodent data, our results suggest a pain‐induced mismatch of increased motivational drive with a lack of increased hedonic responses. This mismatch is discussed as perhaps reflecting a failed coping attempt, which is potentially relevant for chronic pain patients.